The modelling prediction of haul road surface deflection - Coffey, J.; Ghadimi, Behzad; Nikraz, Hamid; Rosano, Michele (Elsevier, 2018)
Haul road pavement design is often completed through application of axisymmetric linear-elastic modelling. This may be implemented either through the derivation of cover curves employing the California Bearing Ratio, or within linear-elastic modelling completed by commercially available software. In recent years, a significant amount of research has been conducted on the application of the Finite Element Method for the analysis of pavements. A study to determine the accuracy of predicted haul road pavement response made by various linear-elastic and Finite Element Methods was undertaken. The deflected pavement surface profile was measured for three haul road pavement sections utilising terrestrial laser scanning, which also allowed measurement of the tyre/pavement contact geometry. Laboratory testing was completed to define the stiffness of each material through triaxial testing. Results of the field and laboratory testing allowed modelling via each method. Only minor variations were observed between the various linear-elastic modelling approaches that were investigated. In general, the Finite Element Method was found to produce the most accurate predictions. These findings provide the impetus for further investigation and the use of Finite Element Method for haul road pavement modelling.